Altered purinergic signaling in the tumor associated immunologic microenvironment in metastasized non-small-cell lung cancer. Issue 3 (December 2015) - Schmid, Severin; Kübler, Markus; Korcan Ayata, C.; Lazar, Zsofia; Haager, Benedikt; Hoßfeld, Madelon; Meyer, Anja; Cicko, Sanja; Elze, Mirjam; Wiesemann, Sebastian; Zissel, Gernot; Passlick, Bernward; et al.
Highlights: We present first human data on purinergic signaling in the tumor associated immunologic microenvironment in lung cancer. The ectonucleotidase CD39/ENTPD1 is upregulated in bronchoalveolar lavage cells in NSCLC, especially in metastatic disease. Potential anti-neoplastic effects of ATP and ADP are undermined due to increased degradation. The purinergic receptors P2 × 7, P2 × 4 and P2Y1 are upregulated in bronchoalveolar lavage cells in NSCLC with distant metastasis. Abstract: Objectives: Purines are well-known as intracellular sources for energy but they also act as extracellular signaling molecules. In the recent years, there has been a growing interest in the therapeutic potential of purinergic signaling for cancer treatment. This is the first study to analyze lung purine levels and purinergic receptors in non-small-cell lung cancer (NSCLC) patients. Materials and methods: In this prospective clinical trial we enrolled 26 patients with NSCLC and 21 patients with chronic obstructive pulmonary disease (COPD) without signs of malignancy. The purine concentrations were analyzed in bronchoalveolar lavage fluid (BALF) using fluorescent/luminescent assays. Expression of purinergic receptors and ectonucleotidases were analyzed using real time quantitative polymerase chain reaction (RT-qPCR). Results: Patients with NSCLC have significantly lower ATP and ADP concentrations in BALF than patients with COPD ( p  = 0.006 and p  = 0.009). Expression of the ectonucleotidase CD39 is significantly higher in BAL cells from cancer patients compared to COPD ( p  = 0.001) as well as in metastasized tumors compared to non-metastasized tumors ( p  = 0.009). Receptor-analysis revealed a higher expression of P2X4 ( p  = 0.03), P2X7 ( p  = 0.001) and P2Y1 ( p  = 0.003) in BAL cells of tumors with distant metastasis. Conclusion: Our data suggests a role for CD39 in lung cancer tumor microenvironment, influencing tumor invasiveness and metastasization. Potentially the increased degradation of ATP and ADP leads to a subversion of their anti-neoplastic effects. Furthermore P2Y1, P2X4 and P2X7 receptors are upregulated in BAL cells in metastatic disease. Our findings might facilitate the identification of new therapeutic targets for cancer immunotherapy.